Decreased 5-hydroxymethylcytosine levels are associated with TET2 mutation and unfavorable overall survival in myelodysplastic syndromes. Issue 11 (November 2013) - Liu, Xiaoliu; Zhang, Guangsen; Yi, Yan; Xiao, Le; Pei, Minfei; Liu, Sufang; Luo, Yunya; Zhong, Haiying; Xu, Yunxiao; Zheng, Wenli; Shen, Jiankai
Abstract The clinical significance and mechanisms of TET2 are not well defined in myeloid malignancies. We detected TET2 mutations and assayed its catalyzing conversion product 5-hydroxymethylcytosine (5-hmC) in 61 Chinese patients with MDS. Ten patients were identified to have TET2 mutations (16.4%). 5-hmC levels in patients with MDS with TET2 mutations were significantly lower than in those without mutations, and CD34+ cells of patients with MDS exhibited a lower 5-hmC content than that of controls. TET2 expression and 5-hmC in patients with MDS with P15 methylation were both significantly lower than in those without P15 methylation. We did not observe a correlation between TET2 mutations and overall survival (OS) in MDS. Interestingly, we found that patients with MDS with higher 5-hmC levels or in lower risk groups of the Revised International Prognostic Scoring System (IPSS-R) had a longer overall survival, suggesting that 5-hmC levels may be a new molecular marker for prognostic assessment of MDS and that revised IPSS criteria are also applicable to the risk categories of Chinese patients with MDS.